Is Universal Financial Education Putting the Cart Before the Horse? - Simms, Kathryn (Journal of Economics and Behavioral Studies, 2014)
This study evaluates the effectiveness of extant financial education in the United States (i.e., employer-provided education, financial education in high school, and financial education in college) via linear regression and logistic regression analyses conducted on data from the 2012 National Financial Capability Study (NFCS). It concludes that although formal financial education is associated with improved financial literacy above and beyond general educational attainment, employer-provided education and financial education in US high schools are frequently associated directly or indirectly with increased odds of an adverse personal financial event (i.e., foreclosure, bankruptcy, or being underwater). Financial education in college is either not significant or is indirectly associated with reduced odds of some these adverse events. Given these findings, it seems that generating and evaluating rigorous empirical evidence about effective methods and curriculums for teaching financial education should be an immediate policy priority rather than requiring universal financial education in haste. However, requiring universal financial education may be a worthy long-term goal, after these more immediate policy needs are achieved. These findings and recommendations contribute to the literature by helping to resolve relatively intense debate among researchers about the effectiveness of financial education via the first study that examines the efficacy of financial literacy in a nationally representative, US database.